CHANGES IN HEMODYNAMICS OF THE CARDIOVASCULAR SYSTEM IN PATIENTS WITH FIBROSIS ALVEOLITIS - Khusainova Munira Alisherovna; Burxonov Zuhriddin Alisherovich; Khabibullayev Ibrokhimkhon Ilyosxonovich; Eliyeva Elnura Oybekovna (Journals Park Publishing, 2022)
Interstitial lung diseases (ILD) are mainly chronic diseases of the lung tissue, manifested by inflammation and disruption of the structure of the alveolar walls, endothelium of the pulmonary capillaries, perivasal and perilymphatic tissues. A characteristic symptom of interstitial lung diseases is shortness of breath, which is a reflection of pulmonary insufficiency. Nonspecific interstitial pneumonia (NSIP) is idiopathic interstitial pneumonia. This disease is much less common than idiopathic pulmonary fibrosis (ILF). Most of the patients are women aged 40 – 50 years, who do not have any known causes or interdependencies. Similar disorders are observed in connective tissue diseases (in particular, systemic scleroderma or autoimmune myositis), some forms of lung diseases associated with the use of medications and hypersensitive pneumonitis. Diseases of the cardiovascular system in patients with fibrosing osteoliths (FO) have not been studied enough. Currently , a number of papers have been published concerning the course of this interstitial disease with simultaneous damage to the cardiovascular system. In patients with combined pathology, there was a tendency of aggravation of desaturation and fibrosis on the processes of myocardial remodeling, on the occurrence of arrhythmias and progression of arterial hypertension (AH), coronary heart disease (CHD), leading to to aggravate circulatory insufficiency and respiratory insufficiency (1-3). There is evidence of the influence of oxidative stress (4,5), systemic inflammation, endothelial dysfunction (6,7) on the progression of cardiac diseases in fibrosing alveolitis. However, some features of the course of this comorbid pathology remain unspecified. It is also interesting to develop algorithms for the diagnosis and treatment of patients with these combined diseases, which determines the relevance of studying this problem.
Keywords: fibrosing alveolitis; diseases; cardiovascular system